“Pretty as a peach” - Nicola Jones; Sandra Pitcher (Communicare)
South Africa’s media are often touted as lacking ethics in favour of sensationalism (Cronin, 2010). Wasserman (2007) argues that this could be a consequence of the increased circulation of daily tabloids in the country, which has been a result of an emerging new public that was marginalised by the mainstream press of the apartheid era. However, by taking this argument forward, one becomes entrenched in the wrongful assumption that tabloids are a journalistic evil, and are the epitome of “bad journalism” (Ornekring & Jonssen, 2004). This paper uses the example of the Sunday Times and City Press newspapers’ coverage of Oscar Pistorius’ arrest and bail application in February 2013 to demonstrate how two of South Africa’s most widely read traditional Sunday newspapers represented Pistorius in the same manner as You magazine, South Africa’s most widely read English tabloid style magazine. The paper acknowledges that tabloid-style reporting is not necessarily as “bad” as its critics maintain, but argues that ethically, reporting could (and should) have been handled differently. The paper analyses the stereotyped representation of Steenkamp and Pistorius in all three publications, and following the work of Clifford Christians (2009), uses these examples to highlight problems with the traditional utilitarian frameworks that govern modern news reporting.